Customer Guidance for Pajarakan Pawnship Customers on the Digital Service Application - Junaedy, Deddy; Maulidinsalam, Muh; Ramdhani, Rizki Alif; sholihin, Moh (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the form of assistance provided by Pegadaian Pajarakan to customers in using the Digital Service application as a technology-based financial service innovation. The background of this study is based on the low digital literacy of some customers, which results in suboptimal application utilization. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that assistance is carried out through socialization, direct training, and the provision of consulting services to help customers understand the application's features. Supporting factors for the success of assistance are customer enthusiasm, employee support, and easy access to technology. Meanwhile, obstacles faced include limited understanding of digital technology among elderly customers and limited communication facilities. The conclusion of this study is that effective assistance can increase the utilization of the Digital Service application and strengthen customer trust in Pegadaian services. This study implies that digital literacy needs to be continuously improved so that the transformation of digital-based financial services can run optimally.